THE ROLE OF THE KHALWATIYAH SAMMANIYAH TAREKAT IN PROMOTING POLITICAL ETHICS IN MAROS REGENCY - Jufri, Andi; Rosmini, Rosmini; Tahir, Muh.; Abdul Majid, Latifah (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
This study examines the role of the Khalwatiyah Sammaniyah Tarekat in promoting political ethics in Maros Regency. As a long-established Sufi order in Indonesian society, the Khalwatiyah Sammaniyah Tarekat plays a significant role in shaping political behavior and morality at the local level. The research explores the contributions of this Sufi order in promoting ethical political practices in Maros. A descriptive qualitative approach was employed, with data collected through in-depth interviews with religious leaders (mursyid of the Khalwatiyah Sammaniyah Tarekat), local stakeholders, and community members affiliated with the order. The study also incorporates relevant literature on the history and principles of the Khalwatiyah Sammaniyah Tarekat, political ethics, moral development theories, and the role of Sufi orders in the Indonesian sociopolitical context. Findings indicate that the Khalwatiyah Sammaniyah Tarekat actively promotes values such as simplicity, tolerance, and honesty, which are essential for fostering ethical political behavior. This study offers insight into how religious and spiritual institutions contribute to the development of a more ethical political culture in the Maros Regency.